Grow the Plant!: An Environmental-Themed Board Game as A Sustainable Living Learning Medium for Elementary School Students - Nisa, Fika Khoirun; Fahminnansih, Fenty; Erdiana, Setya Putri (Jurnal Pendidikan Progresif, 2023)
Grow the Plant!: An Environmental-Themed Board Game as A Sustainable Living Learning Medium for Elementary School Students. Objectives: This research aims to enhance awareness and understanding of sustainability issues through an enjoyable educational game at the UNESA Laboratory Elementary School. Methods: This research employs the Design Thinking method with qualitative data analysis. There were 20 participants aged 8-12 years who participated in answering the research questionnaire. Data is presented and described based on the percentages obtained from the questionnaire results. Findings: This research indicates that 90% of the users of the "Grow the Plant!" board game better understand the importance of plants for environmental sustainability and examples of actions in caring for plants in daily life. Conclusion: Through a board game approach, children can develop awareness and commitment to fostering a positive attitude towards the environment, stimulate their interest in plant cultivation, and provide a foundational understanding of the importance of sustainable living Keywords: board game, sustainable living, elementary school.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202318